2008
DOI: 10.1016/j.biopsych.2008.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hippocampal Brain-Derived Neurotrophic Factor Restores Motivational and Forced Swim Performance After Corticosterone

Abstract: Background-Alterations in cellular survival and plasticity are implicated in the neurobiology of depression, based primarily on the characterization of antidepressant efficacy in naïve rodents, rather than on models that capture the debilitating and protracted feelings of anhedonia and loss of motivation that are core features of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
147
2
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 182 publications
(167 citation statements)
references
References 49 publications
16
147
2
2
Order By: Relevance
“…Figure 1d illustrates the total dose of CORT in mg/kg per rat per day consumed at days sampled during the 50 mg/ml phase of CORT exposure, indicating that the level of CORT the rats were exposed to ranged from approximately 12.5-7.5 mg/kg across days and decreased in direct relation to their increase in weight. The total dose at the end of the exposure period is similar to that previously reported for adult rats, and that maintains high levels of circulating CORT Gourley et al, 2008a).…”
Section: Corticosterone Exposuresupporting
confidence: 84%
“…Figure 1d illustrates the total dose of CORT in mg/kg per rat per day consumed at days sampled during the 50 mg/ml phase of CORT exposure, indicating that the level of CORT the rats were exposed to ranged from approximately 12.5-7.5 mg/kg across days and decreased in direct relation to their increase in weight. The total dose at the end of the exposure period is similar to that previously reported for adult rats, and that maintains high levels of circulating CORT Gourley et al, 2008a).…”
Section: Corticosterone Exposuresupporting
confidence: 84%
“…These and related findings suggest a role for BDNF in the etiology and treatment of depression. On the other hand, chronic stress exposure decreases hippocampal cyclic adenosine monophosphate (cAMP) response element-binding protein (CREB) phosphorylation (pCREB) (13). CREB, in turn, regulates several targets involved in activity-dependent neuronal plasticity, including BDNF (13).…”
Section: The Mechanisms Of Electroconvulsive Stimuli In Brdu-positivementioning
confidence: 99%
“…On the other hand, chronic stress exposure decreases hippocampal cyclic adenosine monophosphate (cAMP) response element-binding protein (CREB) phosphorylation (pCREB) (13). CREB, in turn, regulates several targets involved in activity-dependent neuronal plasticity, including BDNF (13). Finally, we reported that repeated electroconvulsive stimuli treatment increased BDNF protein levels in the hippocampus in rats repeatedly treated with ACTH (4).…”
Section: The Mechanisms Of Electroconvulsive Stimuli In Brdu-positivementioning
confidence: 99%
“…Human recombinant BDNF (Chemicon) dissolved in sterile saline in a concentration of 0.4 mg/mL (Gourley et al 2008b) was used, with 0.2 mL/site at AP +2.0, DV À2.5, ML 60.1 (Gourley et al 2008a) infused over 2 min with needles left in place for 2 min after infusion.…”
mentioning
confidence: 99%
“…Several studies indicate BDNF has behavioral effects for several days after infusion into the striatum (Horger et al 1999), ventral tegmental area (Lu et al 2004), hippocampus (Shirayama et al 2002;Gourley et al 2008b), and prefrontal cortex (Berglind et al 2007(Berglind et al , 2009). Therefore, we utilized a single-infusion protocol: Food restriction resumed on day 5 after surgery, at which point mice appeared active.…”
mentioning
confidence: 99%